2006
DOI: 10.1074/jbc.m512072200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Responses to Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) and CFTRΔ508 in the Lung

Abstract: Cystic fibrosis (CF), a common lethal pulmonary disorder in Caucasians, is caused by mutations in the cystic fibrosis transmembrane conductance regulator gene (CFTR) that disturbs fluid homeostasis and host defense in target organs. The effects of CFTR and ⌬508-CFTR were assessed in transgenic mice that 1) lack CFTR expression (Cftr induced genes encoding heat shock proteins and other chaperones but did not activate the endoplasmic reticulum-associated degradation pathway. RNAs encoding proteins that directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 105 publications
1
29
2
1
Order By: Relevance
“…An overlap with human CF cells would be unexpected and was not found. A recent study has also been reported that was limited to genomic changes in whole mouse lung tissue in response to either wild type or mutant human CFTR (22). Again no parallels occurred with the proteomic changes reported here in human lung CF epithelial cells.…”
Section: Quantitative Comparison Of Silver-stained and Radiolabeled Fcontrasting
confidence: 49%
“…An overlap with human CF cells would be unexpected and was not found. A recent study has also been reported that was limited to genomic changes in whole mouse lung tissue in response to either wild type or mutant human CFTR (22). Again no parallels occurred with the proteomic changes reported here in human lung CF epithelial cells.…”
Section: Quantitative Comparison Of Silver-stained and Radiolabeled Fcontrasting
confidence: 49%
“…Affymetrix Microarray Suite 5.0 was used to scan and quantitate the gene chips under default scan settings. Hybridization data were subjected sequentially to normalization, transformation, filtration, and functional classification and pathway analysis as previously described (50,51). Data analysis was performed with BRB Array Tools software package (http://linus.nci.nih.gov/BRB-ArrayTools.html).…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies of genomic responses indicate that mouse respiratory epithelial cells from both CF models had similar constitutive overexpression of genes influencing several regulatory processes (81,82), but ⌬F508-CF mice had "a primary disturbance in expression of genes regulating redox and antioxidant systems" (82). Hence, comparisons between ⌬F508-CF and UNC-CF mouse pancreas phenotypes may provide insight into CFTR genotype-phenotype correlations and illustrate how seemingly minor differences in exon 10 mutations of the CFTR gene may exert individual effects on cellular processes.…”
mentioning
confidence: 99%